PENGEMBANGAN MEDIA MINIATUR EKOSISTEM AIR PADA PEMBELAJARAN TEMATIK TEMA 5 EKOSISTEM DI KELAS V SD - Hilda Lizayanti; Umar Darwis (Jurnal Cakrawala Ilmiah, 2024)
This study aims to develop miniature water ecosystem media for thematic learning on the theme of 5 ecosystems in class V SD. This research is research development (Research and Development) using the ADDIE development procedure which consists of 5 stages. In this study, researchers carried out the ADDIE development model only up to the development stage. The instrument used to collect data was a questionnaire or questionnaire given to several expert validators, namely media expert validators, material expert validators, learning expert validators and student responses. The total score obtained from the validation of media experts, namely 91.6, from the validation of material experts, namely 91.6, from learning experts is 96 and from student responses obtained a score of 97. The average score from the assessment of experts, namely 94, 05. From this score it can be said that the water ecosystem miniature media developed is "Very Eligible" for use in the learning process.